2002
DOI: 10.1164/rccm.2106029
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke-induced Airway Hyperresponsiveness Is Not Dependent on Elevated Immunoglobulin and Eosinophilic Inflammation in a Mouse Model of Allergic Airway Disease

Abstract: Epidemiologic studies suggest that children raised in homes of cigarette smokers have a higher incidence of asthma than children who are raised in homes of nonsmokers. We sought to develop an experimental model to understand the mechanisms involved. Female BALB/c mice were paired with male DO11.10 ovalbumin (OVA)-T cell receptor hemizygous (+/-) mice such that the offspring were either transgene positive (+/-) or negative (-/-). Mice were exposed to either air or mainstream cigarette smoke (100 mg/m(3) total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 59 publications
7
51
0
Order By: Relevance
“…Consistent with our data, greater inner airway wall thickness in infants who died of sudden infant death syndrome and who were born to mothers who smoked during pregnancy also suggests airway remodeling following in utero smoke exposure (10). The findings of Barrett et al (1), who report that exposure to sidestream smoke in a transgenic mouse model genetically predisposed to asthma was not associated with the development of allergic sensitization, further reinforce alternative mechanisms, such as pulmonary structural changes, as the possible mechanism for asthma in in utero smoke-exposed offspring. In contrast, some studies have reported higher IgE levels in the children of smoking parents (39).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our data, greater inner airway wall thickness in infants who died of sudden infant death syndrome and who were born to mothers who smoked during pregnancy also suggests airway remodeling following in utero smoke exposure (10). The findings of Barrett et al (1), who report that exposure to sidestream smoke in a transgenic mouse model genetically predisposed to asthma was not associated with the development of allergic sensitization, further reinforce alternative mechanisms, such as pulmonary structural changes, as the possible mechanism for asthma in in utero smoke-exposed offspring. In contrast, some studies have reported higher IgE levels in the children of smoking parents (39).…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Fig. 8B, treatment of mice with CS stimulated the methacholine-dependent increase in airway resistance (airway hyperresponsiveness to methacholine), as previously reported (5,27), and this response could be suppressed by the concomitant treatment of animals with PC-SOD (Fig. 8B).…”
Section: Effect Of Combination Application Of Pc-sod With Ipratropiumsupporting
confidence: 83%
“…Therefore, it is possible that one of the factors that contribute to the exaggerated airway narrowing in patients with COPD may be an abnormality in the nature of airway smooth muscle. Experimental evidence has been reported that chronic exposure to cigarette smoke augments the in vivo responsiveness of airways to cholinergic agonists in rats (Xu et al, 1993), guinea pigs (Wu and Lee, 1999), and mice (Barrett et al, 2002). Although little is known concerning the effect of cigarette smoking in vivo on the contractility of airway smooth muscle ex vivo, we previously demonstrated that subacute exposure to cigarette smoke in vivo caused an augmented ACh-induced contraction with an upregulation of RhoA in bronchial smooth muscle ex vitro (Chiba et al, 2005).…”
Section: Introductionmentioning
confidence: 78%